'What was your blood sugar reading this morning?': representing diabetes self-management on Facebook - Hunt, Daniel; Koteyko, Nelya (SAGE, 2015)
Social networking sites have swiftly become a salient venue for the production and consumption of neoliberal health discourse by individuals and organisations. These platforms offer both opportunities for individuals to accrue coping resources and a means for organisations to promote their agendas to an online audience. Focusing specifically on diabetes, this article examines the representation of social actors and interactional styles on three organisational Pages on Facebook. Drawing on media and communication theories, we situate this linguistic analysis in relation to the communicative affordances employed by these organisations as they publish content online. Diabetes sufferers are represented as an at-risk group whose vulnerabilities can be managed through forms of participation specific to the respective organisation. More popular diabetes Pages draw on the opportunities for social interaction afforded by Facebook and combine informational and promotional content to foster communication between the organisation and its audience. By encouraging reflexive management of diabetes risks, these Pages contribute to the construction of ‘biological citizens’ who interweave habitual interactions on social networking sites with responsible self-care, consumption of health information and health activism.